2016
DOI: 10.1007/s40618-016-0474-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of papillary thyroid carcinoma in childhood and adolescence: an Italian multicenter study on 250 patients

Abstract: Pediatric patients are likely to benefit from a tailored surgical strategy. Uniformly offering patients total thyroidectomy seems to be an overly radical approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 16 publications
3
43
2
1
Order By: Relevance
“…A recent study on 250 children/AYAs with DTC concluded that treatment should be tailored to the patient's clinical presentation . Conservative surgery should be used for patients with tumors limited to one lobe, <2 cm in diameter, and with neither lymph node involvement nor distant metastasis.…”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study on 250 children/AYAs with DTC concluded that treatment should be tailored to the patient's clinical presentation . Conservative surgery should be used for patients with tumors limited to one lobe, <2 cm in diameter, and with neither lymph node involvement nor distant metastasis.…”
Section: Differentiated Thyroid Carcinomamentioning
confidence: 99%
“…[3][4][5] A recent study on 250 children/AYAs with DTC concluded that treatment should be tailored to the patient's clinical presentation. 83 Conservative surgery should be used for patients with tumors limited to one lobe, <2 cm in diameter, and with neither lymph node involvement nor distant metastasis. All patients were alive after a median 5.8 years, and in appropriately selected patients, conservative surgery proved safe and oncologically effective.…”
Section: Conservative Managementmentioning
confidence: 99%
“…If involvement of lateral cervical lymph nodes is suspected clinically or by preoperative imaging studies, this should be confirmed by FNA prior to undertaking lateral neck lymph node dissection. Surgery, especially if a compartment‐focused lymph node resection is indicated, should ideally be performed by an experienced surgeon to minimize complications . The ATA guidelines task force defines an experienced, high‐volume surgeon as one who performs at least 30 cervical surgeries annually …”
Section: Surgical Approachmentioning
confidence: 99%
“…In a national multicenter retrospective review of 250 pediatric patients in Italy treated for papillary thyroid carcinoma in a 14-year period, it was concluded that total thyroidectomy seems to be an overly radical approach [12]. The rate of recurrent disease was 12 % (30/250) with the vast majority of recurrences (96.6 %) occurring in the total thyroidectomy group.…”
Section: Improvements In Selected Areas Of Pediatric Oncology Advancementioning
confidence: 99%